Arctic Species Trend Index: Tracking Trends in Arctic Marine Populations - McRae, L; Delnet, S.; Gill, M.; Collen, B. (Conservation of Arctic Flora and Fauna (CAFF), 2012)
Track the trends in Arctic marine mammals, birds and fish through this analysis of the marine dataset in the revised Arctic Species Trend Index (ASTI).